Teacher training - Holden, Susan (Modern english : Modern english, 1979)
This book is designed for use both on training courses and by the individual reader. The content covers a range of learner age groups from young learners to adults within both mainstream education and language institute contexts. The aim is to encourage teachers to feel confident to develop their personal abilities within a framework of critical thinking about teaching english today as a global and ever-changing international language the varied contexts in which teachers and students interact.
Keywords: English language -- Foreign speakers; English teachers -- Training of; Teacher training -- Great Britain